Dinuclear Cobalt Complexes with a Decadentate Ligand Scaffold: Hydrogen Evolution and Oxygen Reduction Catalysis. Issue 1 (26th November 2015) - Di Giovanni, Carlo; Gimbert‐Suriñach, Carolina; Nippe, Michael; Benet‐Buchholz, Jordi; Long, Jeffrey R.; Sala, Xavier; Llobet, Antoni
Abstract: A new decadentate dinucleating ligand containing a pyridazine bridging group and pyridylic arms has been synthesized and characterized by analytical and spectroscopic techniques. Four new dinuclear cobalt complexes featuring this ligand have been prepared and thoroughly characterized both in the solid state (X‐ray diffraction) and in solution (1D and 2D NMR spectroscopy, ESI‐MS, and electrochemical techniques). The flexible but stable coordination environment provided by the ligand scaffold when coordinating Co in different oxidation states is shown to play a crucial role in the performance of the set of complexes when tested as catalysts for the photochemical hydrogen evolution reaction (HER) and chemical oxygen reduction reaction (ORR). Abstract : Ten arms are better than one : A decadentate dinucleating ligand with a pyridazine bridging group and pyridylic arms was synthesized. The ligand provides a flexible but stable coordination environment that plays a crucial role in the catalytic performance of the complexes in the photochemical hydrogen evolution reaction (HER) and chemical oxygen reduction (ORR) (see figure).